2018
DOI: 10.3390/su10051391
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Soil Fungal Community in a Three-Year Green Garlic/Cucumber Crop Rotation System in Northwest China

Abstract: Abstract:A decreased soil biological environment in terms of an unstable microbial population and diversity index is primarily caused by intensive continuous cropping systems. In this study, a crop rotation system was established to evaluate the soil fungal diversity using a pyrosequencing-based analysis during three successive growing seasons (2013, 2014, and 2015) under a field pot investigation. We found that overall green garlic/cucumber rotational effects increased cucumber productivity under these growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 78 publications
(59 reference statements)
2
18
1
Order By: Relevance
“…Previous studies have indicated a reduction in fungal diversity in plots under monocropping due to reduced organic matter content (Manici and Caputo 2009). Fields under monoculture resulted in a build up of fungal pathogens compared to rotation plots (Ding et al 2018). This could probably explain our findings because trials were established on plots where the previous crop was also potato.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have indicated a reduction in fungal diversity in plots under monocropping due to reduced organic matter content (Manici and Caputo 2009). Fields under monoculture resulted in a build up of fungal pathogens compared to rotation plots (Ding et al 2018). This could probably explain our findings because trials were established on plots where the previous crop was also potato.…”
Section: Discussionmentioning
confidence: 98%
“…Celery is a kind of vegetable with strong allelochemicals. Rotation with crops with stronger allelochemicals can effectively improve the richness and diversity of soil fungi (Ding et al, 2018). It has also been shown that continuous cropping can increase the fungal richness of crop rhizosphere soil (Meng et al, 2012;Zhou and Wu, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Soil microorganism analysis was determined according to a previously described method by Ding et al . Soil DNA was extracted from 0.5 g mixed soil samples using a soil DNA kit (OMEGA, Bio‐Tek, Norcross, GA, USA) according to the manufacturer's protocols.…”
Section: Methodsmentioning
confidence: 99%